Caryl Phillips’s novels: a reminder of a forgotten issue - Mani, Manimangai; Jujar Singh, Hardev Kaur (Universiti Putra Malaysia Press, 2013)
Throughout history, colonization and the competition for power among the European races triggered the mass migration of many races in the world. However, it cannot be denied that the most affected race were the Blacks who were forced into slavery. The establishment of slavery is the biggest injustice of colonisation, where the Blacks were treated as commercial objects. Slavery turned into a lucrative business where it involved licensing and diplomatic controls between many European powers. Therefore, this phenomenon has borne many writings on human migrations and assimilation in their new homes. Most of these writings are the works of writers who themselves were affected by this movement across continents. Caryl Phillips is one of the writers who made this issue as a persistent theme in all his works. Phillips’s works were never a mere narration on migrants and migrations. More than that, it is an attempt to retell an unfortunate incident in the chapters of the world history about the mass displacement of a particular race. Phillips, who was born in the Caribbean Islands and raised in England, often depicts the feelings of rootlessness and the nostalgia for a homeland in the characters in his novels. However, what seems like an affinity to lurk around a rich story material has a potent and hidden agenda. This paper will show that Phillips, a descendent of slaves, often harps on these long forgotten issues with a deliberate and definitive motive. A scrutinised study on his novels will show that it is indeed his wish to remind the world and the descendents of the Black slaves not to forget the past.